2014
DOI: 10.3389/fpubh.2014.00105
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Substance Use and HIV Treatment Factors Associated with Neurocognitive Impairment among People Living with HIV/AIDS

Abstract: Neurocognitive (NC) impairment remains prevalent among people living with HIV (PLWH) and may be exacerbated by alcohol and drug use. This cross-sectional study assesses the degree to which alcohol and other drug use, time from HIV diagnosis to treatment, and years living with HIV affect three areas of NC functioning among HIV-seropositive adults. NC functioning in 370 PLWH living in Miami, FL was assessed using the Auditory Verbal Learning Test, the Short Category Test, Booklet Format, and the Color Trails Tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
15
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 62 publications
1
15
0
1
Order By: Relevance
“…In prior studies (Anderson et al, 2015; Attonito et al, 2014; Becker et al, 2011), cognitive deficits have been associated with risky behaviors, poor medication adherence, and treatment disengagement (Anand et al, 2010; Shrestha et al, 2015; Verdejo-Garcia and Perez-Garcia, 2007; Vo et al, 2014). Given the relationship between NCI and higher HIV risk behaviors, this is an important group of PWUD who might benefit from PrEP.…”
Section: Discussionmentioning
confidence: 96%
“…In prior studies (Anderson et al, 2015; Attonito et al, 2014; Becker et al, 2011), cognitive deficits have been associated with risky behaviors, poor medication adherence, and treatment disengagement (Anand et al, 2010; Shrestha et al, 2015; Verdejo-Garcia and Perez-Garcia, 2007; Vo et al, 2014). Given the relationship between NCI and higher HIV risk behaviors, this is an important group of PWUD who might benefit from PrEP.…”
Section: Discussionmentioning
confidence: 96%
“…Prior evidence has demonstrated that HIV-infected PWUDs display a wide range of cognitive deficits including problems with executive function, attention, memory, new learning, information-processing speed, and visual-spatial perception, that have significant impact on HIV risk behaviors and risk-reduction intervention outcomes. Furthermore, the presence of cognitive impairment may be associated with the disease process (AIDS-related dementia), drug use history, or relatively poor lifestyle (Anand, Springer, Copenhaver, & Altice, 2010; Anderson, Higgins, Ownby, & Waldrop-Valverde, 2015; Attonito, Devieux, Lerner, Hospital, & Rosenberg, 2014; Becker, Thames, Woo, Castellon, & Hinkin, 2011; Byrd et al, 2011; Ezeabogu, Copenhaver, & Potrepka, 2012; Heaton et al, 2011; Meade, Conn, Skalski, & Safren, 2011; Schouten, Cinque, Gisslen, Reiss, & Portegies, 2011; Shrestha, Weikum, Copenhaver, & Altice, 2016; Thaler, Sayegh, Kim, Castellon, & Hinkin, 2015; Woods, Moore, Weber, & Grant, 2009; Zhou &Saksena, 2013) and may be disruptive to participation in treatment services, including HIV prevention, treatment engagement, and medication adherence, which must be accounted for during behavioral intervention development and adaptation (Bates, Pawlak, Tonigan, & Buckman, 2006; Fishbein et al, 2007; Huedo-Medina, Shrestha, &Copenhaver, 2016; Shrestha & Copenhaver, 2016; Shrestha, Huedo-Medina, & Copenhaver, 2015; Verdejo-Garcia & Perez-Garcia, 2007; Vo, Schacht, Mintzer, & Fishman, 2014). …”
mentioning
confidence: 99%
“…Our data confirms that central obesity is associated with impaired verbal and auditory working memory, and reduced capacity for decision-making. These cognitive functions are associated with the higher-order thinking required to conduct safer sex practices and health management behaviors, such as ART adherence [29]. There are now many associations that may link increased obesity to changes in cognitive performance; however the mechanisms remain highly speculative.…”
Section: Discussionmentioning
confidence: 99%